Global health, global surgery and mass casualties: II. Mass casualty centre resources, equipment and implementation. Issue 1 (13th January 2020) - Aguilera, Sergio; Quintana, Leonidas; Khan, Tariq; Garcia, Roxanna; Shoman, Haitham; Caddell, Luke; Latifi, Rifat; Park, Kee B; Garcia, Patricia; Dempsey, Robert; Rosenfeld, Jeffrey V; Scurlock, Corey; et al.
Abstract : Trauma/stroke centres optimise acute 24/7/365 surgical/critical care in high-income countries (HICs). Concepts from low-income and middle-income countries (LMICs) offer additional cost-effective healthcare strategies for limited-resource settings when combined with the trauma/stroke centre concept. Mass casualty centres (MCCs) integrate resources for both routine and emergency care—from prevention to acute care to rehabilitation. Integration of the various healthcare systems—governmental, non-governmental and military—is key to avoid both duplication and gaps. With input from LMIC and HIC personnel of various backgrounds—trauma and subspecialty surgery, nursing, information technology and telemedicine, and healthcare administration—creative solutions to the challenges of expanding care (both daily and disaster) are developed. MCCs are evolving initially in Chile and Pakistan. Technologies for cost-effective healthcare in LMICs include smartphone apps (enhance prehospital care) to electronic data collection and analysis (quality improvement) to telemedicine and drones/robots (support of remote regions and resource optimisation during both daily care and disasters) to resilient, mobile medical/surgical facilities (eg, battery-operated CT scanners). The co-ordination of personnel (within LMICs, and between LMICs and HICs) and the integration of cost-effective advanced technology are features of MCCs. Providing quality, cost-effective care 24/7/365 to the 5 billion who lack it presently makes MCCs an appealing means to achieve the healthcare-related United Nations Sustainable Development Goals for 2030.